(untitled) - REES, PAUL K.; SPARKS, FRED W. (USA, 1957)
1.The formula fundamental operations and simple equations / 2.The formula / 3.Some definitions /4.Algebraic combinations rulesof signs / 5.The equation / 6.Solution of linear equations in one unknown / 7.Solving problems by means of equations / 8.The four fundamental operations / 9.Addition / 10.Subtraction / 11.Multiplication of monomials / 12.Symbols of grouping / 13.Multiplication involving polynomials / 14.Zero in multiplication / 15.Division of monomials / 16.Zero in multiplication / 17.Zero in the division process / 18.Division involving polynomials / 19.Special products and factoring / 20.The product of two binomials /21.The square of a polynomial / 22.Factors of a trinomial / 23.Trinomials that are perfect squares / 24.Factors of a binomial / 25.Common factors / 26.Factoring by grouping / 27.Trinomials reducible to the difference of two squares / 28.Fractions and fractional equations / 29.Reduction of fractions / 30.Multiplication of fractions / 31.Division of fractions / 32.The lowest common multiple / 33.Addition of fractions / 34.Complex fractions / 35.Equations that involve fractions / 36.problems leading to equations that involve fractions /37.Funtions and graphs / 38.Constans and variables / 39.Funtions and funtional notation / 40.Graphical representation of functions / 41.Linear funtions / 42.Graphical representation of statistics / 43.Simultaneous linear equations / 44.Linear equations in two unknowns / 45.Solution of two linear equations in two unknowns graphical method / 46.Elimination of a variable by addition or subtraction / 47.Elimination of a variable by substitution / 48.Three linear equations in three unknowns / 49.Problems leading to sistems of linear equations / 50.Exponents and radicals / 51.Laws of positive integral exponens / 52.Negative integral exponents / 53.Roots of number / 54.Fractional exponents / 55.Simplification of exponential expressions / 56.Simplification of radical expressions / 57.Rationalizing denominators / 58.Addition of radicals / 59.Changing the order of a radical / 60.Quadratic equations / 61.Solution of pure quadratic equations / 62.Solution of quadratic equations by factoring / 63.Solution of quadratic equations by completing the square / 64.Complex number / 65.The quadratic formula / 66.Facts about the roots of quadratic equations / 67.Equations that involve radicals of the second order / 68.Equations in quadratic form / 69.Sistems of quadratic equations in two variables / 70.Graphs of quadratic equations in two variables / 71.Solution of pairs of equations involving quadratics in two variables / 72.Pairs of equations in two variables involving a linear and a quadratic equation / 73.Elimination by addition or subtraction / 74.Two equations of the type / 75.Pairs of quadratic equations solvable by substitution / 76.Symmetric equations / 77.Ratio proportion and variation / 78.ratio proportion variation / 79.Logarithms / 80.Common or briggs logarithms / 81.The characteristic and mantissa / 82.Rounding off a number / 83.Use of the table to obtain the mantissa / 84.Use of tables to find n when log n is given / 85.Properties of logarithms / 86.Logarithmic computation / 87.Logarithms to bases other than / 88.Exponential and logarithmc equations / 89.The progressions / 90.Arithmetic progressions / 91.The last term of an arithmetic progression / 92.The sum of an arithmetic progerssion / 93.Simultaneous use of the formulas for l and s / 94.Arithmetic means / 95.Geometric progressions / 96.The last term of a geometric progression / 97.The sum of a geometric progression / 98.Geometrics means / 99.Infinite geometric progressions / 100.The binomial theorem / 101.The binomial formula / 102.The rth term of the binomial formula
Incluye indice analitico pag.303
Keywords: 1.ALGEBRA \ 2. ALGORITMOS